Prevalence of burnout among frontliners in Kota Kinabalu district health office during covid-19 and its association with perceived social and organisational support. - Abraham Chiu En Loong; Mohd Yusof Ibrahim; Abdul Rahman Ramdzan (Universiti Putra Malaysia, 2023)
Introduction: The COVID-19 pandemic has placed an unprecedented workload and strain on Malaysia’s health system and healthcare workers. Prolonged chronic work stress coupled with unsupportive working environment can translate to serious psychological impacts such as burnout. This study aims determine the prevalence of burnout among frontliners under Kota Kinabalu Health District Office and its association with perceived social and organisational support during COVID-19 pandemic. Methods: A cross-sectional study was conducted among 397 healthcare workers from May 2021 to June 2021 using Copenhagen Burnout Inventory, Multidimensional Scale of Perceived Social Support, and Perceived Organisational Support (POS) scale. Chi-squared was used to determine its association. Results: The prevalence of overall burnout was 43.8%, 68.8% for personal burnout, 45.6% for work-related burnout, and 26.4% for client-related burnout. Using Chi-square, this study found that several sociodemographic characteristics of HCWs such as younger age, unmarried, working outside of the clinic, working as doctors and health inspectors, and lesser years of working experience were significantly associated with higher prevalence of burnout in our study. The study showed a drastic increase in prevalence of burnout in HCWs compared to other studies done during pre-pandemic period. Burnout was significantly associated with lower perceived organisational and social support. Conclusion: Efforts and interventions by policy makers and administrative heads are needed to reduce the prevalence of burnout among HCWs during the pandemic.